Cupping therapy: influence in the improvement hamstring flexibility - Agostinho, Ana (2022)
Objectives – To verify the influence of cupping therapy on hamstring flexibility in healthy individuals with hamstring shortening, associated with a stretching exercise protocol. Method – It was applied for the Active Knee Extension and Sit and Reach tests in two groups of participants: the experimental group (n=6) and control group (n=6) to evaluate hamstring flexibility. In the experimental group, it was applied cupping therapy and stretching exercises. In the control group, it was only performed stretching exercises. After three weeks (three interventions each week) the groups were reassessed. Results – There was an improvement in both groups between the first and last evaluations. However, the comparison between the groups revealed no statistical differences. Discussion – The results indicate that there is no evidence of the use of cuppings as a complementary therapy in a stretching program to improve flexibility in comparison to the exclusive use of stretching exercises in the selected sample. We foresee the development of more studies to evaluate the effects and the efficacy of cupping therapy as well as the use of larger samples. Conclusion – Both groups showed improvements in hamstring flexibility. Cupping therapy did not demonstrate significant change as a complementary therapy to stretching.